FRAILTY PREVENTION AMONG OLDER AFRICAN AMERICANS. (11th November 2018) - Fritz, H; Tarraf, W; Lysack, C
Abstract: Older African Americans (OAA) are at risk for becoming frail in later life, which increases their risk of early death, disability, and institutionalization. Intervening to bolster physical and socio-emotional capacities at the first signs of frailty (i.e., during the pre-frailty stage) could reduce or prevent the development of frailty. However, we lack effective frailty prevention interventions, and there is little guidance about how best to prevent/delay frailty development among at-risk older adults. We present data and preliminary findings from the development and in-progress evaluation of the Frailty Prevention Program (FPP). The FPP is a transdisciplinary collaboration between primary care physicians and occupational therapy (OT). Over a two-year period providers will identify prefrail older OAA in the primary care setting and refer up to n = 200 prefrail OAA to receive either OT intervention to target the behavioral, psychosocial, physiologic, and environmental factors that contribute to frailty development (delivered 1x month for 4 months) or usual care. The OT intervention is standardized in that, for each patient, the OT evaluates the health behaviors, performance skills, performance patterns, and environmental characteristics that contribute to deficits in health promotion and prevention, activity and participation, and social engagement. Program feasibility acceptability, and cost sustainability measures are being collected throughout the study. Data to evaluate the primary and secondary outcomes is being collected at baseline and at months 4, 7, and 10 months post baseline. We are also collecting qualitative data to better understand older OAA perceptions of frailty risk, and the notion of prefrailty.